2020
DOI: 10.1002/jcp.30052
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation alleviates endoplasmic reticulum stress during porcine oocyte in vitro maturation by upregulating zinc transporters

Abstract: Endoplasmic reticulum (ER) stress is a major contributor to embryonic development failure. Mammalian oocytes have a high risk of exposure to cellular stress during in vitro embryo production. We investigated the effects of zinc supplementation during in vitro maturation under ER stress. We evaluated cumulus expansion, embryonic development derived by parthenogenetic activation, reactive oxygen species, protein expression of X‐box binding protein 1 (XBP1), and expression of genes related to ER stress. Supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…XBP1 is commonly used as a marker of ER stress, both in vivo and in vitro [ 49 , 50 ]. In line with the present study, zinc treatment during IVM reported significantly reduced expression levels of XBP1 in matured porcine oocytes; improved blastocyst formation rates; and significantly decreased gene expression of Caspase 3 and ER stress-related genes such as XBP1 , binding protein ( BiP ), PTPN1 , and ATF4 [ 51 ]. The increase of XBP1 is suggestive of an activation of the ER stress response through the Inositol-requiring transmembrane kinase endoribonuclease-1α ( IRE1α ), one of the UPR branches.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…XBP1 is commonly used as a marker of ER stress, both in vivo and in vitro [ 49 , 50 ]. In line with the present study, zinc treatment during IVM reported significantly reduced expression levels of XBP1 in matured porcine oocytes; improved blastocyst formation rates; and significantly decreased gene expression of Caspase 3 and ER stress-related genes such as XBP1 , binding protein ( BiP ), PTPN1 , and ATF4 [ 51 ]. The increase of XBP1 is suggestive of an activation of the ER stress response through the Inositol-requiring transmembrane kinase endoribonuclease-1α ( IRE1α ), one of the UPR branches.…”
Section: Discussionsupporting
confidence: 86%
“…In cases of severe ER stress, apoptotic cell death was induced by phosphorylated e IF2α , which further triggers ATF4 , which induces apoptosis [ 60 ]. Our previous study showed that a reduction of ER stress-related genes and Caspase 3 resulted in improved in vitro embryo development [ 51 ]. These results revealed that miR-210 is involved in alleviating apoptosis by decreasing ATF4 and Caspase 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Ovaries were obtained from Landrace prepubertal gilts at a local pig abattoir and placed at 32–37 °C in 0.9% normal saline solution. Oocyte collection and IVM were performed as previously explained [ 33 , 35 , 42 , 43 ]. In brief, Oocytes were collected from follicles (3–6 mm) utilizing a 10-mL syringe.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, oocytes were denuded with 0.1% hyaluronidase in TALP-HEPES medium and stained with 5 μg/mL Hoechst-33342 in TALP-HEPES for 10 min. Oocytes with dark homogenous ooplasm with polar body were selected for SNCT [ 33 ]. Furthermore, the first polar body and elemental Metaphase II (MII) chromosome were enucleated using an aspiration glass pipette.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation